Insights on Extent of Effectiveness, Trend, and Gap in Existing Frameworks for e-Procurement System - N Madhusudan; L. Manjunatha Rao (International Journal of Electrical and Computer Engineering (IJECE), 2016)
With the advancement of technologies, the organization and business applications are witnessed with the increasing trends to adopt cut edge technologies to normalize their business process.  However, this trend was not observed much on the e-Procurement system, where the existing users still place the purchase order using conventional web-based approach that cannot address various ongoing challenges in eProcurement system. This paper attempts to review the existing trends and challenges of web-based eProcurement system and discusses that with the adoption of cloud computing as present trend, such ongoing issues of eProcurement can be addressed. The paper discusses the effectiveness of the existing techniques with interpretation of research gap.